If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4z + 12 + -2z = 2 Reorder the terms: 12 + 4z + -2z = 2 Combine like terms: 4z + -2z = 2z 12 + 2z = 2 Solving 12 + 2z = 2 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + 2z = 2 + -12 Combine like terms: 12 + -12 = 0 0 + 2z = 2 + -12 2z = 2 + -12 Combine like terms: 2 + -12 = -10 2z = -10 Divide each side by '2'. z = -5 Simplifying z = -5
| 0.6x+7=8 | | 6.2/12.71 | | -11t=5-6t | | -14.5(-1.5)=-31.5 | | 6z+8=-22 | | 19÷1/3 | | 3/4x=a | | 8-2x=-24 | | 11=23-2j | | 19=1/3p | | 6n-2=4n+8 | | 17=-2(3h-4) | | 8(4a+2b)= | | 5z+9=6z | | Sin(35)=4/x | | 10(s+6)=100 | | 9/c=6/10 | | 6x/16 | | 6-3n=-3 | | 9/c=6/1p | | -3a+28+5a=2a-7a | | 7x+8=6x+2 | | 3x+2x=37 | | (x+50)+3x+90=180 | | 3+3(x-6)=-24 | | 4h=-5+5h | | 6(2x+3)=18 | | 8t+4=6t | | 48-4p=4 | | 238+x=-183 | | 12-4x+11=11 | | 18=2n+8 |